A Bibliometric Review of Knowledge Management Systems in Organizational Learning and Innovation - Judijanto, Loso; Berliani, Teti; Aidhi, Akhmad Al (Eastasouth Institute, 2024)
This study employs a bibliometric analysis to explore the evolution of research themes within the field of organizational learning and innovation from 2006 to 2014. Utilizing VOSviewer for network visualization, the research identifies key thematic shifts over time, tracing the trajectory from foundational aspects such as information technology and tacit knowledge to more complex constructs like organizational innovation and leadership. The analysis reveals a gradual shift towards integrating technology with organizational capabilities, highlighting how evolving technologies influence learning environments and innovation processes. Practical implications are discussed, suggesting ways organizations can adapt to these trends to enhance knowledge management and innovation. Theoretical contributions are also noted, emphasizing the study’s role in enriching the understanding of the dynamic interplay between organizational knowledge processes and innovation. Limitations of the bibliometric method and the potential subjectivity of visual data interpretation are acknowledged, setting the stage for future research to build upon these foundational findings.